Hubungan Pengetahuan, Sikap, dan Peran Orang Tua Terhadap Keberhasilan Toilet Training pada Anak Usia 4-6 Tahun di Taman Kanak- Kanak (TK) Desa Wisata Kuta Mandalika, Lombok Tengah, NTB - Warni, Sri; Jauhari, Pebrian; Cahyadi Tri Setiawan, Nyoman; Qurratu Ainin, Dina (Peneliti.net, 2024)
One aspect of a child's growth and development is independence. Independence is a child's ability to think and do things on their own to meet their needs and no longer rely on others. One example of this is toilet training independence. Factors that can impact the progress of carrying out latrine preparing incorporate parental information, disposition, mental state, schooling, work and the development of the youngster's age. This study aims to determine how parents' knowledge, attitudes, and involvement influence the success of toilet training in children aged 4-6 in the kindergarten of the Kuta Mandalika tourist village in West Nusa Tenggara, Central Lombok. The strategy utilized is a cross sectional review with an example size of 195 respondents with an examining method specifically basic irregular testing. The measurable test utilized is the chi square test. That's what the outcomes showed (55.4%) latrine preparing was ineffective. It was observed that the degree of parental information was bad (51.8%), the mentality of guardians was bad (55.9%), and the job of guardians was bad (61.5%). In Kindergarten Kuta Mandalika Tourist Village, Central Lombok, West Nusa Tenggara, a bivariate analysis reveals that there is a relationship between knowledge and the success of toilet training (p=0.000), parental attitudes toward the success of toilet training (p=0.003), and the role of parents and the success of toilet training (p=0.000). There is a huge connection between information, mentalities, and the job of guardians on the outcome of latrine preparing in kids matured 4-6 years at the Kuta Mandalika The Tourism Village Kindergarten, Central Lombok, West Nusa Tenggara.